Temporal landscapes : a thesis presented in partial fulfilment of the requirements for the degree of Master of Fine Arts at Massey University, Wellington, New Zealand - Jacobson, Shelley (Massey University, 2009)
Temporal Landscapes is a research project concerned with culture-nature relations in the context of contemporary industrial land use in New Zealand; explored visually through the photographic representation and presentation of gold mining sites – former, current and prospective – in the Hauraki region. In the current period of industrial capitalism, featuring the mass exploitation of natural resources, nature is commonly thought of as subservient to humankind. This stance, with its origin in scientific ideology of the 17th Century, is interesting to consider in relation to contemporary notions of landscape, and the ‘ideal’ in nature. In New Zealand, a balance is being sought between interests of sustainability and conservation, and of industry and economy. This is not to say that industry opposes environmental safeguards; in contrast, sustainable management including the rehabilitation of land post-industrialisation is integral to modern mining practice in New Zealand. With this emphasis on controlled industrial progress, two key factors emerge. Firstly, this level of control implicates itself as a utopian vision, and secondly, industrialisation is advocated as a temporary situation, with industrial land as transitory, on the path to rehabilitation. The research question of Temporal Landscapes asks; in considering contemporary industrial land use in New Zealand within a utopian framework – focussing specifically on gold mining in the Hauraki Region – has our ideal in nature become that of a controlled, even post-industrial, landscape? The photographic representation of these sites offers a means to explore and express their visual temporality. With the expectation of industrial sites as fleeting and rehabilitated sites as static utopias, it would seem that this industrial process is a kind of contemporary ideal. Presented as a flickering projection piece, 23 Views. (Prospective gold mining site, Golden Valley, Hauraki, 2008 / Martha gold mine and Favona gold mine, Waihi, Hauraki, 2008), and a set of selectively lit prints, Untitled I. (Garden, pit rim walkway, Martha gold mine, Waihi, Hauraki, 2008), Untitled II. (View of pit, former Golden Cross gold mine, Waitekauri Valley, Hauraki, 2008), and Untitled III. (View of water treatment pond, former Golden Cross gold mine, Waitekauri Valley, Hauraki, 2008), they act as landscapes of partial comprehension.
Keywords: Gold mining; Hauraki; Photographic representation; Fields of Research::410000 The Arts::410200 Visual Arts and Crafts Studies::410203 Photography studies